GAMBARAN FAKTOR PENYEBAB KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI RSUD Prof. Dr. MARGONO SOEKARJO PURWOKERTO TAHUN 2010 - Tri Susilawati; Arlyana Hikmanti; Linda Yanti (Viva Medika, 2011)
Infant Low Birth Weight (LBW) is a newborn whose weight at birth of less than 2500 grams. The cause of LBW in general because of several factors, includingmaternal factors such as disease, age, parity, socioeconomic circumstances. Fetalfactors such as infection of the fetus and multiple pregnancies, as well asenvironmental factors. In hospitals Prof. Dr. Margono Soekarjo Purwokertoshowed the incidence of low birth weight in the period in 2012 recorded 591 LBWinfants and in the period of 2010 recorded 811 LBW infants.This study aims to describe the causes of the incident Infant Low Birth Weight(LBW) in hospitals Prof. Dr. Margono Soekarjo Purwokerto in 2010This research is descriptive quantitative study approach documentation. Samplingin this study using a quota sampling, sample of this research is all Infant LowBirth Weight (LBW) were born in hospitals Prof. Dr. Margono SoekarjoPurwokerto in 2010 as many as 100 cases. Measuring instruments used mastertable and type of data is secondary data. Data were analyzed using univariate.The result showed the majority of LBW was lbw as many as 55 respondents(55%), preeclampsia group of 65 respondents (65%), bleeding antepartum asmany as 76 respondents (76%), have a reproductive age as much as 39respondents (39%), has primiparous parity as much as 53 respondents (53%), hasa range of pregnancy respondent is <2 years of 60 respondents (60%) and has amild anemia as many as 40 respondents (40%).LBW among other factors causing preeclampsia, antepartum hemorrhage,reproductive age, parity primiparous pregnancy spacing <2 years old, mildanemia. Keywords: Infant Low Birth Weight (LBW), Causes